Glut-1 expression in small cervical biopsies is prognostic in cervical cancers treated with chemoradiation. (February 2017) - Kanjanapan, Yada; Deb, Siddhartha; Young, Richard J.; Bressel, Mathias; Mileshkin, Linda; Rischin, Danny; Hofman, Michael S.; Narayan, Kailash; Siva, Shankar
Abstract: Background/purpose: Chemoradiation (CRT) is standard therapy for locally advanced cervical cancer (LACC). However, there is a lack of biomarkers to identify patients at high relapse-risk. We examine metabolic (glucose transporter-1 [Glut-1]), hypoxic (hypoxia inducible factor [HIF-1α]; carbonic anhydrase [CA-9]) and proliferative (Ki-67) markers for prognostic utility in LACC. Materials/methods: 60 LACC patients treated with CRT had pre-treatment biopsies. Immunohistochemistry was performed for Glut-1, HIF-1a and CA-9, to generate a histoscore from intensity and percentage staining; and Ki-67 scored by percentage of positive cells. For each biomarker, treatment response and survival was compared between low and high-staining groups by logrank testing and multivariate analyses. Results: High Glut-1 expression was associated with inferior progression-free survival (PFS), (hazard ratio [HR] 2.8, p  = 0.049) and overall survival (OS), (HR 5.0, p  = 0.011) on multifactor analysis adjusting for stage, node positivity, tumour volume and uterine corpus invasion. High Glut-1 correlated with increased risk of distant failure (HR 14.6, p  = 0.001) but not local failure. Low Glut-1 was associated with higher complete metabolic response rate on post-therapy positron emission tomography scan (odds ratio 3.4, p  = 0.048). Ki-67 was significantly associated with PFS only (HR 1.19 per 10 units increase, p  = 0.033). Biomarkers for hypoxia were not associated with outcome. Conclusions: High Glut-1 in LACC is associated with poor outcome post CRT. If prospectively validated, Glut-1 may help select patients for more intensive treatment regimens.